Faktor-Faktor Yang Menyebabkan Terjadinya Pembiayaan Bermasalah Pada Akad Al-Qardh di Koperasi Syariah Majelis Ta’lim Masjid Al-Arif Kota Bandung - Syaripudin, Muhammad Agus (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2024)
The occurrence of problematic financing will have a negative impact on the financial condition of cooperatives and affect the income of sharia cooperatives. Therefore, with the phenomenon of Al-Qardh financing problems at the Sharia Cooperative of the Ta'lim Council of Al-Arif Mosque in Bandung, researchers are interested in conducting research entitled Factors Causing the Occurrence of Problematic Al-Qardh Financing in the Sharia Cooperative of the Ta'lim Al-Arif Council of Bandung City. The research method used by researchers is descriptive qualitative method. Al-Qardh financing is one of the products in the Sharia Cooperative Cooperative Majelis Ta'lim Masjid Al-Arif, this product also has many enthusiasts. There is a problematic financing that occurs in the Sharia Cooperative of the Ta'lim Council of Al-Arif Mosque which is triggered by two factors, namely internal and external factors. Internal factors include the lack of careful analysis and application of the values contained in the 5C principle by the cooperative to the character of members so that there are some members who are difficult when collecting their obligations, while the external factors are the impact of the Covid-19 pandemic and the lack of ability of members to manage money in the business they run, causing losses that have an impact on the difficulty of paying bill obligations to the cooperative.